2018
DOI: 10.1152/japplphysiol.00050.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of healthy aging on cerebral blood flow, CO2 reactivity, and neurovascular coupling during exercise

Abstract: We sought to make the first comparisons of duplex Doppler ultrasonography derived measures of cerebral blood flow during exercise in young and older individuals, and to assess whether healthy ageing influences the effect of exercise on neurovascular coupling (NVC) and cerebral vascular reactivity to changes in carbon dioxide (CVR). In ten healthy young (23±2yr; mean±SD) and nine healthy older (66±3yr) individuals, internal carotid artery (ICA) and vertebral artery (VA) blood flows were concurrently measured, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 83 publications
0
19
2
Order By: Relevance
“…However, two studies of working memory (Madureira et al, 2017) and reading (Stefanidis et al, 2019) based tasks did not find any age-related differences on CBFv response. Several TCD-based studies investigating motor (Orlandi & Murri, 1996), visual (Flück et al, 2014;Nowak-Flück et al, 2018;Zaletel et al, 2005) and working memory (Vermeij et al, 2014) found reduced rather than increased responses.…”
Section: Context Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…However, two studies of working memory (Madureira et al, 2017) and reading (Stefanidis et al, 2019) based tasks did not find any age-related differences on CBFv response. Several TCD-based studies investigating motor (Orlandi & Murri, 1996), visual (Flück et al, 2014;Nowak-Flück et al, 2018;Zaletel et al, 2005) and working memory (Vermeij et al, 2014) found reduced rather than increased responses.…”
Section: Context Of Literaturementioning
confidence: 99%
“…Healthy aging is associated with a number of key changes in cerebral function (Murman, 2015). Healthy older adults demonstrate reduced hemispheric lateralization to cognitive tasks (Cabeza, 2002), posterior-anterior shift of cognitive processes (McCarthy et al, 2014), and variable changes to the magnitude of the response to cognitive stimulation Jamadar, 2020;Nowak-Flück et al, 2018;Vermeij et al, 2014). These changes were initially thought to be compensatory, given that cognitive function was comparable to younger adults despite these differences (Berlingeri et al, 2013;Reuter-Lorenz & Cappell, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally distributed data are presented as mean (SD), while non-normally distributed data are presented as median [interquartile range]. Assuming a 6% SD for NVC as Nowak-Fluck et al., 31 the minimal detectable difference between the groups would be 7% with a sample size of 12 patients in each group, at 80% power and 5% alpha. Assuming a 0.35%/mmHg SD for normalized gain at 0.1 Hz during the repeated squat-to-stand manoeuvre as Smirl et al., 32 the minimal detectable difference between the groups would be 0.28%/mmHg with a sample size of 25 patients in each group, at 80% power and 5% alpha.…”
Section: Methodsmentioning
confidence: 99%
“…In adults, impaired neurovascular coupling has been described in different pathological conditions like stroke, hypertension, hypotension, autonomic dysfunction, Alzheimer’s disease, diabetes, and traumatic brain injury (Duschek and Schandry, 2004; Girouard and Iadecola, 2006; Azevedo et al, 2011; Vetri et al, 2012; Phillips et al, 2014; Jang et al, 2017). In addition, also smoking and healthy aging are associated with a negative effect on neurovascular coupling (Boms et al, 2010; Tarantini et al, 2017; Nowak-Fluck et al, 2018).…”
Section: Spatiotemporal Studiesmentioning
confidence: 99%